the KEEFEKTIVITASAN REMDESIVIR UNTUK TERAPI SARS-COV-2 - Devantoro, Mohammad Ridho; Wijaya, Wilson Saputra; Anggriani, Hayu Ari (Essence of Scientific Medical Journal; Vol 19 No 1 (2021): Volume 19 No. 1 (Januari - Juni 2021) Essential: Essence of Scientific Medical Journal, 2021)
Background : SARS-CoV 2 belongs to the coronaviridae family and the genus ?-CoV which has a single positive RNA chain with major structural proteins. namely Spike (S) which will bind to its receptor, Angiotensin Converting Enzyme 2 (ACE2). SARS-CoV2 has become a pandemic with a total number of cases worldwide reaching 1,777,666 people. Therapies used today are hydrocloroquin and macrolides. both work as immunomodulators. but hydrocloroquin has resistance. therefore we need therapy that has a target mechanism for other RNA virus molecules Method : The writing is based on a journal review that is relevant to the topic to be discussed, the selected journal is a journal in the last 5 years. Based on the journals that have been collected and analyzed and compared between journals, 22 journals from a total of 30 journals are used. keywords used were ‘SARS-CoV-2, Hydroxychloroquine, azithromycin, and Remdesivir   Discussion: SARS-CoV-2 is a ?-coronavirus (CoV) that belongs to family Coronaviridae, subfamily Orthocoronavirinae, has a single strand positive RNA. Like SARS-CoV, this virus requires Angiotensin-Converting Enzyme 2 (ACE-2) receptor for its entry, found in the lower respiratory tract. The virus enters the cell, antigen presented to the Antigen Presenting Cells, causing cytokine storm, ARDS, and multiple organ dysfunction ends with death. To fight SARS-CoV-2, treatment still basis on other coronaviruses research, SARS and MERS. From earlier researches, a combination of hydroxychloroquine and azithromycin become the drug of choice. This combination can reduce replication also viral load, including one from these researches shows that 100% of the samples cured of SARS-CoV-2. Unfortunately, the mechanism behind these medications are unknown, so research is needed to find potent anti-SARS-CoV-2 medicines and work on viral RNA. In this literature, we focus on SARS-CoV-2 promising treatments such as Remdesivir, as an alternative for hydroxychloroquine and azithromycin. Conclusion: Remdesivir has antiviral activity in vitro dan in vivo against viral RNA that cannot be done by Chloroquine.